(untitled) (International relations and international law Journal, 2018)
Even before the declaration of the state independence of the Republic of Kazakhstan United Kingdom took a special interest in the Kazakh land. Since the second half of the XVI century until the middle of the XIX century about ten Englishmen visited the Kazakh land for various purposes. It was a time when a number of European countries have shown interest in establishing trade relations with Central Asian countries. It’s no secret that the favorable geographical position of Kazakhstan is an effective route for England, which at that time claimed to trade hegemony. Today, the UK’s interests in the Caspian region abut on the economy and trade. For European countries, heavily dependent on the petroleum feedstock, the issue of their interests in the Caspian region is one of the top priorities. Of course, for this end the presence of the British capital in the Caspian part is a prerequisite. Therefore, since 1990-1991, various British companies have begun to actively invest oil and gas industry of the country and provide loans at different rates and terms. In this regard, we can observe an active involvement of the British oil magnates such as British Petroleum, British Gas and Shell in the Caspian projects. Likewise, we can not say that this partnership is not effective for Kazakhstan. Key words: multi-vector policy, natural resources, the Caspian region, geopolitical interest, oil and gas sector, investment, mutually beneficial cooperation.